Alginate Hydrogel Adsorbents in Adsorption of Inorganic and Organic Pollutants: A Review - Suresh, Selvaraj; Ravichandran, S.; Y. Pandya, Ishan; Sreeja Mole, S.S.; Boselin Prabhu, S.R.; Prashanth, G.K. (Asian Journal of Chemistry, 2022)
The present review discusses various alginate hydrogel adsorbents with unique adsorption performance in environmental remediation. Novel alginate composites were developed with, high swelling capacity and capable of adsorbing toxic inorganic and organic pollutants. Alginate hydrogel adsorbents were developed with a single network and double network structure with excellent adsorption ability in removal of toxic inorganic and/or organic pollutants. Alginate with single or double network composite hydrogels were developed when alginate was combined with graphene/chitosan/polymer to get superior adsorbents in removal of toxic pollutants. Acrylic acid/alginate hydrogel in recent studies are efficient in the elimination of inorganic and organic contaminants. This review will generate interest to researchers to develop novel alginate composite hydrogels with unique properties in the adsorption of toxic inorganic, organic contaminants. This work provides a worthy challenge and the future possibility of designing novel alginate materials for various applications.